Qualitative analysis of informational consumption and political attitudes of youth in relation to democracy and citizenship in southern Bolivia - Durán Sandoval, Romy Jimena (2025)
In Bolivia, there is a scarcity of updated research regarding the information consumption habits of young people. This article presents the findings of an analysis of the informational consumption and the current political attitudes of secondary school students from middle and lower socioeconomic backgrounds in the city of Sucre, the capital of Bolivia, in relation to democracy, pluralism, and citizenship. Using a qualitative approach, in-person group interviews were conducted in public, subsidised, and private schools, employing a card game created by researchers from the University of Chile. The process included coding, inductive systematization based on Grounded Theory, Thematic Analysis, the Constant Comparative Method, and qualitative analysis. The results show that the information consumption of 16- and 17 year-olds is incidental and focused on social media, which they prefer despite recognizing their lack of credibility, as well as maintaining their interest in public affairs and considering that traditional media are not independent. Secondary school students support democracy, distrust Bolivian politicians and rulers, and demand equitable access to job opportunities. Their critical attitude is vulnerable to invisibility and political neglect. Young people face a lack of public policies that support the development of plural citizenship and promote media literacy.